Engineering polydimethylsiloxane with two-dimensional graphene oxide for an extremely durable superhydrophobic fabric coating. Issue 71 (13th July 2016) - Yan, Hong; Zhou, Hui; Ye, Qun; Wang, Xiaobai; Cho, Ching Mui; Tan, Angeline Yan Xuan; Xu, Jianwei
Abstract : A type of nanostructured material comprising reduced graphene oxide (RGO) modified polydimethylsiloxane (PDMS) for fabric coating is described. Abstract : A type of nanostructured material comprising reduced graphene oxide (RGO) modified polydimethylsiloxane (PDMS) for fabric coating is described. RGO modified PDMS was prepared through an aryl radical assisted addition reaction, followed by hydrosilylation with Si–H terminated PDMS or poly(dimethylsiloxane- co -methylhydrosiloxane) (PDMS- co -PHMS) in the presence of a catalytic amount of Pt catalyst. The introduction of a trace amount of RGO to cross-link with PDMS or PDMS- co -PHMS led to a significant improvement in the hydrophobicity (water contact angle > 150°) of textile fabrics. The superhydrophobicity of the fabric coating, which was readily achieved by a facile dipping coating process, is long-term resistant to strong acids, corrosive alkalis, hot water and 200 cycles of laundry. This type of RGO modified PDMS or PDMS- co -PHMS coating materials makes use of the inherent morphological anisotropy of fabrics which latter provides a hierarchical roughness on the micro scale to further enhance the surface hydrophobicity, showing potential use in various textile applications.